Metabolism of Thiosulfate and Tetrathionate by Heterotrophic Bacteria from Soil - Trudinger, P. A. (1967)
Two heterotrophic bacteria that oxidized thiosulfate to tetrathionate were isolated from soil. The enzyme system in one of the isolates (C-3) was constitutive, but in the other isolate (A-50) it was induced by thiosulfate or tetrathionate. The apparent K(m) for oxygen for thiosulfate oxidation by A-50 was about 223 μm, but, for lactate oxidation by A-50 or thiosulfate oxidation by C-3, the apparent K(m) for oxygen was below 2 mm. The oxidation of thiosulfate by A-50 was first order with respect to oxygen from 230 μm. The rate of oxidation was greatest at pH 6.3 to 6.8 and at about 10 mm thiosulfate, and it was strongly inhibited by several metal-binding reagents. Extracts of induced A-50 reduced ferricyanide, endogenous cytochrome c, and mammalian cytochrome c in the presence of thiosulfate. A-50, once induced to oxidize thiosulfate, also reduced tetrathionate to thiosulfate in the presence of an electron donor such as lactate. The optimal pH for this reaction was at 8.5 to 9.5, and the reaction was first order with respect to tetrathionate. There was no correlation between the formation of the thiosulfate-oxidizing enzyme of A-50 and the incorporation of thiosulfate-sulfur into cell sulfur. Thiosulfate did not affect the growth rate or yield of A-50.